2014
DOI: 10.1007/s12013-014-0083-5
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Behind the Inhibition of Lung Adenocarcinoma Cell by Shikonin

Abstract: Shikonin, a natural naphthoquinone isolated from a traditional Chinese medicinal herb, can exert inhibitory effect on tumor cell growth. However, little has been known concerning the effect of shikonin on lung adenocarcinoma cell and underlying mechanisms. In the present study, we investigated the effect of shikonin on the proliferation, cell cycle arrest, and apoptosis in human lung adenocarcinoma cells. We found that shikonin significantly suppressed the proliferation of lung adenocarcinoma cells compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 32 publications
0
19
0
1
Order By: Relevance
“…It is effective in treating different kinds of cancers, including breast, prostate, ovarian and thyroid cancers, Ewing sarcoma, and myelomonocytic lymphoma [595][596][597][598][599][600]. Shikonin exerts anti-cancer effects mainly by inducing apoptosis, necroptosis, autophagy, cell cycle arrest, and by inhibiting cell proliferation, growth and metastasis [593,601,602].…”
Section: Shikoninmentioning
confidence: 99%
See 1 more Smart Citation
“…It is effective in treating different kinds of cancers, including breast, prostate, ovarian and thyroid cancers, Ewing sarcoma, and myelomonocytic lymphoma [595][596][597][598][599][600]. Shikonin exerts anti-cancer effects mainly by inducing apoptosis, necroptosis, autophagy, cell cycle arrest, and by inhibiting cell proliferation, growth and metastasis [593,601,602].…”
Section: Shikoninmentioning
confidence: 99%
“…Shikonin is reported to inhibit cell growth by inducing cell cycle arrest and promoting apoptosis in human NSCLC A549, gallbladder cancer NOZ and EHGB-1, esophageal cancer EC109, and epidermoid carcinoma A-431 cells [601,[603][604][605]. It can also induce necroptosis via autophagy inhibition in human NSCLC A549 cells [593], and through ROS overproduction in human nasopharyngeal carcinoma 5-8F, and glioma SHG-44, U87 and U251 cells [606,607].…”
Section: Shikoninmentioning
confidence: 99%
“…2 The parasite mediated immune suppression increases the risk of collateral deadly infections like HIV. 9 It is extended as an antioxidant, 10 antimicrobial, [11][12][13] anti-fungal, 14 anti-lung cancer, 15,16 and our recent report against human chronic myeloid leukemia. 4,5 Our group recently reported that acetyl shikonin (AS), natural derivative of shikonin -a naphthoquinone, as a major component in dried root bark of Arnebia nobilis like others.…”
Section: Introductionmentioning
confidence: 99%
“…Caspase-3/7 activation is responsible for the final step of apoptosis (31,32) and reflects the degree of apoptosis in various cancer cells (33). To determine whether the anti-proliferative effect of shikonin was associated with the induction of apoptosis, a fluorescence quantification assay was used.…”
Section: Discussionmentioning
confidence: 99%